2004
DOI: 10.1021/jf049487b
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiadiazole Enhances Resveratrol and Anthocyanin Biosynthesis in Grapevine, Meanwhile Improving Resistance toBotrytis cinerea

Abstract: Pre-harvest multiple treatments of grapevine (cv. Merlot) with the plant activator benzothiadiazole (BTH, 0.3 mM) enhanced trans-resveratrol content in berries by about 40%. An even more striking effect was observed on anthocyanin synthesis, particularly on malvidine 3-glucoside, malvidine 3-(6-O-acetyl)glucoside and malvidine 3-(6-O-p-coumaroyl)glucoside, whose amounts were more than doubled. These data were obtained with a novel and time-saving HPLC method, set up for the simultaneous detection of stilbenes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(123 citation statements)
references
References 48 publications
7
116
0
Order By: Relevance
“…Consistent with our results, accumulation of resveratrol, anthocyanins, and proanthocyanidins was found in grapevine after BTH treatment applied four weeks before the harvest (10, 21). In grapes, the higher phenolic content was linked to the enhanced resistance against Botrytis cinerea in the fruits (10). Preharvest BTH treatment has also given protection against postharvest gray mold in strawberries (15), suggesting that BTH causes long-term changes in secondary metabolism, which might not only improve resistance to pathogens but also influence the nutritional value and bioactive properties of the crop (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, accumulation of resveratrol, anthocyanins, and proanthocyanidins was found in grapevine after BTH treatment applied four weeks before the harvest (10, 21). In grapes, the higher phenolic content was linked to the enhanced resistance against Botrytis cinerea in the fruits (10). Preharvest BTH treatment has also given protection against postharvest gray mold in strawberries (15), suggesting that BTH causes long-term changes in secondary metabolism, which might not only improve resistance to pathogens but also influence the nutritional value and bioactive properties of the crop (22).…”
Section: Resultsmentioning
confidence: 99%
“…What ultimately causes the improved resistance varies, since a different set of secondary metabolites and pathogenesis-related (PR) proteins may be synthesized depending on the plant family and species. However, the accumulation of soluble or cell-wall-bound phenolics has been observed along with enhanced resistance to pathogens in many plants (e.g., 4, 6,10). Benzothiadiazole (BTH), the functional analogue of salicylic acid, has been found to strongly induce defense reactions and production of phenolics (6,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolome data set showed that stilbenes (38, 128, and 230), flavanones (7, 18, 19, 20, 46, 68, 69, 72, 83, and 185), and acylated anthocyanins (12, 13, 22, 35, 36, 58, 60, 81, 107, 112, 115, 127, 215, 237, 247, 280, and 380) are the predominant metabolites that accumulate during withering, with stilbenes and flavonones already implicated in stress responses (Dercks and Creasy, 1989;Adrian et al, 1997;Versari et al, 2001;Bonello and Blodgett, 2003) and a similar role likely for acetylated anthocyanins. The treatment of Merolt grapevine with benzothiadiazole increases the synthesis of trans-resveratrol and anthocyanins, particularly malvidine-3-glucoside and its acylated derivates, and thus enhances resistance to Botrytis cinerea (Iriti et al, 2004). The acetylated anthocyanins that accumulate during withering are mostly coumarate derivates that are important in winemaking because they influence pigmentation and increase light absorption, thus affecting red wine color (Iriti et al, 2004).…”
Section: Integration Of Data Sets (Hypothesis-driven Approach)mentioning
confidence: 99%
“…The treatment of Merolt grapevine with benzothiadiazole increases the synthesis of trans-resveratrol and anthocyanins, particularly malvidine-3-glucoside and its acylated derivates, and thus enhances resistance to Botrytis cinerea (Iriti et al, 2004). The acetylated anthocyanins that accumulate during withering are mostly coumarate derivates that are important in winemaking because they influence pigmentation and increase light absorption, thus affecting red wine color (Iriti et al, 2004). Acylation can also increase anthocyanin activity (Yoshimoto et al, 2001).…”
Section: Integration Of Data Sets (Hypothesis-driven Approach)mentioning
confidence: 99%
“…(Figures 1B (b,c)). Other preharvest chemical treatments such as benzothiadiazole and chitosan (Iriti, Rossoni, Borgo, & Faoro, 2004) increased the content of t-resveratrol in grapes. Although the increase of stilbenes in the grapes could be due to a stress produced to the plants (Roldán, Palacios, Caro, & Pérez, 2003), it also depended on the chemical nature of the compounds applied, such as eugenol which produced the highest increase of stilbenes.…”
Section: Phenolic Compounds Determination By Hplc-dad-msmentioning
confidence: 99%